Exploring the World with the Laser Dedicated to Theodor Hänsch on his 75th birthday (Springer International Publishing, 2018)
This edition contains carefully selected contributions by leading scientists in high-resolution laser spectroscopy, quantum optics and laser physics. Emphasis is given to ultrafast laser phenomena, implementations of frequency combs, precision spectroscopy and high resolution metrology. Furthermore, applications of the fundamentals of quantum mechanics are widely covered. This book is dedicated to Nobel prize winner Theodor W. Hänsch on the occasion of his 75th birthday. The contributions are reprinted from a topical collection published in Applied Physics B, 2016.